Optical properties of Ge-As-S thin films - Tolmachov, I.D.; Stronski, A.V. (Functional Materials, 2009)
Thin Ge-As-S films have been prepared by thermal vacuum evaporation. Optical parameters and thickness values of the films have been calculated basing on transmission spectra. The dispersion dependences of the refractive index have been shown to be described well by the single oscillator model. The optical band gap width has been determined using the Tauc dependence. The non-linear optical properties of the films have been estimated basing on the data obtained. Методом термічного вакуумного випаровування отримано тонкі плівки складу Ge-As-S. Із спектрів пропускання розраховані оптичні сталі та товщини плівок. Показано, що дисперсійні залежності показника заломлення добре описуються одноосциляторною моделлю. 3а допомогою залежності Тауца визначено ширину оптичної забороненої зони. На основі отриманих даних проведено оцінку нелінійних оптичних властивостей плівок. Методом термического вакуумного испарения получены тонкие пленки состава Ge-As-S. Из спектров пропускания рассчитаны толщины пленок и оптические постоянные. Показано, что дисперсионные зависимости показателя преломления хорошо описываются одноосцилляторной моделью. С помощью зависимости Тауца определена ширина оптический запрещенной зоны. На основании полученных данных проведена оценка нелинейных оптических свойств пленок.